Shooting pain - Chai, Wen Lin; Ngeow, Wei Cheong (2009)
Sir, we couldn't help but wonder if there was a common factor that contributed to the unusual manifestation following inferior alveolar nerve blocks. Paul et al.1 described that their patient experienced a sharp pain following the insertion of a dental injection needle. Incidentally, we have also reported such a similar experience whereby one of our patients reported experiencing sharp shooting pain prior to local anaesthesia misadventure.2 We suspect that the piercing of the dental injection needle into the neurovascular bundle causes a breach and this allows the local anaesthetic agent to be percolated into it instead of surrounding it. This local anaesthetic agent is then transported retrogradely to a branch elsewhere, resulting in all of these unusual manifestations. We wonder what would have happened if Paul et al. did not deposit any local anaesthetic agent upon realising their patient was feeling sharp pain?